PEMIMPIN YANG MELAYANI DALAM MEMBANGUN BANGSA YANG MANDIRI - Asep Solikin; Muhammad Fatchurahman; Supardi Supardi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Leadership is a person’s ability to convince and motivate others to do something that are related to the common goals. The leadership involved the process of convincing in determining the goal of organization, motivating the attitude of the participator to reach the goal, convincing to improve their group and culture. Leadership is a formal position, that ask to get facilities and services from the constituents that should be served. Although among the leaders that when they are inaugurated said that the position is a trust, but in fact, there is very little or it can be said almost no leader that truly implementing the leadership from their heart, that is a serving leader. Even that needs to be a note here is how a leader must have a vision in building an independent soul, views, thoughts, attitudes and behaviors of all of the people at one the leader in order to be oriented to the progress and modern, so Indonesia become a big nation and be able to have competition with the other nations in the world. A truly leader always worked hard to improve himself before the leader busy to improve the others. The leader is not only a title or position that given from the outside but something that it grows and evolves from the inside of the person.